Balancing National Security and Data Protection: The Role of EU and US Policy‐Makers and Courts before and after the NSA Affair*. (4th September 2017) - Dimitrova, Anna; Brkan, Maja
Abstract: Based on the unparalleled number of recent data protection reforms triggered by Snowden's revelations on both sides of the Atlantic, this article aims to examine the interplay between the two main transatlantic actors striking the balance between national security and privacy, namely EU and US policy‐makers and courts. We argue, on the one hand, that the NSA affair has opened a window to policy‐makers to pursue reforms in order to attain a level of adequacy of their respective data protection legal regimes. On the other hand, although some data protection reforms have been adopted by legislators in response to courts acting as reformers in the post‐Snowden context, the EU and US courts' approaches to balancing national security and data protection remain diametrically opposite. Drawing upon recent case law, we demonstrate that US courts continue to tilt the balance in favour of national security while EU courts retain their pro‐privacy stance.